Synsätt på smittskydd i svenska häststall - Fuchs, Ellinor (2017)
Today there is a lot of knowledge and information regarding diseases, routines for infectious disease control and measures around contamination. We also know that horse keepers are taking care of infectious disease control in many different ways, but what is it that determines their decision making concerning infectious disease control and what kind of mindset that affects infectious disease control? The purpose of this study is to gain a deeper understanding and insight in horse keepers attitudes about infection control practices as well as hygienic routines in stables, i.e. control the flow of animals and humans, quarantine/isolation, basic hygiene, and see what kind of attitude that affects the level of disease control. The study is based on focus groups with a total of eight experienced horse keepers, from different equestrian sport disciplines; Icelandic horses, trotting horses and riding horses. Horse keepers are from Jämtland and Uppsala. Results: Most horse keepers have a good attitude towards infectious disease control and there are also many who are trying to think about prevention when dealing with infectious diseases. Factors perceived as limitations in order to achieve a higher level of disease control are the stable site and the business economy. Conclusion: In order to draw any major conclusions about the attitudes and approaches regarding the infectious disease control in Swedish horse stables, it would require a greater number of participants/respondents. My study provides more guidance of what one can assume to be the prevailing view in terms of infectious disease control in stables. Keywords: equine infectious diseases, biosecurity, horse keepers.